Analysis and mitigation of nonlinear fiber impairments in high bit rate all-optical orthogonal frequency division multiplexing system / Jassim Kadim Hmood - Jassim Kadim, Hmood (2016)
All-optical orthogonal frequency division multiplexing (AO-OFDM) techniques have been recently considered for optical transmission systems applications. The all-optical solution has obtained an immense interest since it could work beyond the state-of-art electronics speed. However, AO-OFDM systems suffer highly from phase noise that induced by fiber nonlinearities, such as self-phase modulation (SPM), cross-phase modulation (XPM), and four-wave mixing (FWM). This thesis aims to analyze the effects of fiber nonlinearity and proposes new techniques to mitigate their impairments in AO-OFDM systems. At first, an analytical model that evaluates linear and nonlinear phase noises induced by the interaction of amplified spontaneous emission (ASE) noise with SPM, XPM, and FWM phenomena in m-array quadrature-amplitude modulation (mQAM) AO-OFDM transmission systems is developed. This analytical model is able to quantitatively compare the nonlinear phase noise variation due to variations in power of subcarrier, number of subcarriers, transmission distance and subcarrier index. Our results reveal that, in contrast to wavelength division multiplexing (WDM) transmission systems, the nonlinear phase noise induced by FWM dominates over other factors in AO-OFDM systems. Furthermore, it is shown that optical OFDM systems are immune to chromatic dispersion (CD) where the total phase noise decreases with CD effects at high subcarrier power. Four approaches are proposed in this thesis to mitigate the nonlinear fiber impairments in AO-OFDM systems; reducing the power of signal inside fiber, minimizing the interaction time between the subcarriers, reducing peak-to-average power ratio (PAPR), or using phase-conjugated twin waves (PCTWs) technique. In first approach, the power of the signal is reduced by shaping envelope of QAM subcarriers using return-to-zero (RZ) coder to mitigate the nonlinear fiber impairments. In second approach, the interaction time between subcarriers is minimized by shaping the envelopes of QAM subcarriers using RZ coding and making a delay time between even iv and odd subcarriers. Due to the subcarriers are alternately delayed (AD), the AD RZ-QAM AO-OFDM signal is produced after combing all subcarriers. The results reveal that the nonlinear phase noise is significantly mitigated when the time delay is equal to half symbol period. In the third approach, the reduction of peak-to-average power ratio (PAPR) is proposed based on constellation rotation to reduce the nonlinear fiber impairments. The odd subcarriers are modulated with rotated mQAM constellation, while the even subcarriers are modulated with standard mQAM constellation. The results reveal that PAPR is minimized when the angle of rotation is equal to for the 4QAM AO-OFDM system. Finally, in the fourth approach, a new technique to suppress nonlinear phase noise in spatially multiplexed AO-OFDM systems based on PCTWs technique is demonstrated. In this technique, AO-OFDM signal and its phase-conjugated copy are directly transmitted through two identical fiber links. At the receiver, the two signals are coherently superimposed to cancel the phase noise and to enhance signal-to-noise ratio (SNR). The results reveal that the performance of the proposed system is substantially improved as compared with original system.